(3GdeWQ hGdSMGHs - (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s ((3GdMSjf Hf Ydi Hf eMeO GdcGJH s)
(3ChdgG (B:s
(3bGd GHf OQjO gPG cJGH LeYfG ajg eG PcQJg GdYQH ai LGgdjJgG hESdGegG ef hUa GdeWQ hGdSMGH s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddgq s
(3GdfSNI HgG MhGTs
(3fbdJ ef fSNI ebQhAI Ydi CHj SYjO GdSjQGais
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B189 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B32s
Keywords: (3GddZIs